Predicting Patients with Renal Failure using Neural Networks - Nada Yousif Abdulazeez (International Journal of Computers and Informatics, 2026)
Artificial neural network considered as most important in statistic and artificial intelligent that reflex important improvement for future prediction a series of time data from 1999 to 2018, which represent 20 series of time data represent renal failure patients men and women, bath. Results of the research reach predictions in three years represented in the following years (2019-2020-2021). Through results the predictions values have best used way from traditional used way in prediction previously. The documents loosed on researchers from Ibn Seena Hospital in Nenavah Governorate in renal failure.
Keywords: Prediction; Patients; Renal Failure; Neural Networks